The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s41927-018-0018-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic widespread pain in a population-based cohort of patients with spondyloarthritis – a cross-sectional study

Abstract: Background Chronic pain, regional or widespread, is a frequent and multidimensional symptom in arthritis. There is still limited information on chronic pain in spondyloarthritis, which is important to recognize for adequate diagnosis and treatment. Our objective was to study differences in prevalence of chronic widespread pain in two spondyloarthritis subgroups: ankylosing spondylitis (AS) and undifferentiated spondyloarthritis (USpA). Methods A population-based postal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(48 reference statements)
4
10
0
Order By: Relevance
“…The most important difference between men and women in nr-axSpA related to the BASDAI, as a patient-reported disease activity outcome. The amplitude of this difference was slightly lowered by exclusion of nr-axSpA patients with co-morbid fibromyalgia, which was more commonly seen in women, confirming previous analyses [ 30 32 ]. We cannot entirely exclude the possibility that diagnosis of concurrent fibromyalgia might have been missed in some patients, as clinical differentiation between enthesitis and allodynia of fibromyalgia might be challenging in clinical practice.…”
Section: Discussionsupporting
confidence: 87%
“…The most important difference between men and women in nr-axSpA related to the BASDAI, as a patient-reported disease activity outcome. The amplitude of this difference was slightly lowered by exclusion of nr-axSpA patients with co-morbid fibromyalgia, which was more commonly seen in women, confirming previous analyses [ 30 32 ]. We cannot entirely exclude the possibility that diagnosis of concurrent fibromyalgia might have been missed in some patients, as clinical differentiation between enthesitis and allodynia of fibromyalgia might be challenging in clinical practice.…”
Section: Discussionsupporting
confidence: 87%
“…Sex-attributed differences in pain [ 16 , 24 ], disease activity [ 35 ], treatment response [ 36 ], and quality of life [ 37 ] are known in IRDs. In accordance with past findings [ 15 , 38 ], women in this study with SpA reported higher crude pain scores compared with men ( Supplementary Tables S10–S12 , available at Rheumatology online). However, adjustment for disease-specific characteristics (inflammatory and clinical markers) attenuated the observed sex differences in pain in early IRD.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to having continuous peripheral inflammatory input that can cause increased sensitivity in peripheral nociceptors, some individuals may also develop a central sensitization, resulting in hyperalgesia and allodynia (23,24). This could partly explain the high prevalence of CWP (34%) reported in patients with rheumatoid arthritis (RA) (25), and our own previous findings were that almost half (47%) of the patients with AS and USpA reported coexisting CWP (26). According to previous research, increasing pain intensity and spread of pain in multiple body regions, together with psychological and social factors, can result in CWP (27)(28)(29).…”
mentioning
confidence: 94%